Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s13075-023-03118-3
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii alleviates inflammatory arthritis and regulates IL-17 production, short chain fatty acids, and the intestinal microbial flora in experimental mouse model for rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is a systemic chronic inflammatory disease that leads to joint destruction and functional disability due to the targeting of self-antigens present in the synovium, cartilage, and bone. RA is caused by a number of complex factors, including genetics, environment, dietary habits, and altered intestinal microbial flora. Microorganisms in the gut bind to nod-like receptors and Toll-like receptors to regulate the immune system and produce various metabolites, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Members of the Bacteroides genus, prevalent anaerobic gut bacteria, are pivotal in carbohydrate and protein metabolism and play a vital role in the production of SCFAs [ 37 , 38 ], which are integral for energy and modulating immune and inflammatory responses [ 39 ]. The genus Faecalibacterium , especially Faecalibacterium prausnitzii , comprises a considerable portion of the human colon and is renowned for its production of anti-inflammatory SCFAs, such as butyrate [ 40 , 41 ]. This genus is crucial in maintaining intestinal wall integrity and preventing inflammation and other diseases, thereby promoting general health [ 42 ]; these observations have been mirrored in calf research [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Bacteroides genus, prevalent anaerobic gut bacteria, are pivotal in carbohydrate and protein metabolism and play a vital role in the production of SCFAs [ 37 , 38 ], which are integral for energy and modulating immune and inflammatory responses [ 39 ]. The genus Faecalibacterium , especially Faecalibacterium prausnitzii , comprises a considerable portion of the human colon and is renowned for its production of anti-inflammatory SCFAs, such as butyrate [ 40 , 41 ]. This genus is crucial in maintaining intestinal wall integrity and preventing inflammation and other diseases, thereby promoting general health [ 42 ]; these observations have been mirrored in calf research [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…While our in-vitro experiment confirmed PG ’s capacity to generate SCFAs, we observed no significant differences in cecal SCFA levels between non-treated CIA and PG -treated CIA mice. A prior study demonstrated differences in SCFA levels between gut and serum, suggesting the potential systemic transport of SCFAs within the body ( 55 ). Their research revealed an increase in serum butyrate levels upon administering Faeclibacterium prausnitzii , a representative butyrate-producing bacterium, in CIA mice.…”
Section: Discussionmentioning
confidence: 99%